Caring for lesbian and gay people : a clinical guide - Peterkin, Allan; Risdon, Cathy (University of Toronto Press, 2003)
"Allan D. Peterkin and Cathy Risdon begin with an overview of the history of medical relations with lesbian and gay patients, providing advice and guidelines for strengthening the doctor-patient relationship and raising the standard of care for all patients. The book then delves into a range of specific clinical issues, such as risk profiles for particular illnesses, screening for and managing sexually transmitted infections, and HIV treatment in the primary care setting. Subsequent chapters cover a wide range of topics such as mental health care and the effect of homophobia on relationships, same-sex parenting, the role that body image plays in health, and unique populations, such as lesbian and gay ethnoracial minorities, the transgendered, rural lesbian and gay people, and elders. Each chapter includes practical tips (advice on inclusive language, for example) and summaries, along with references of written and online resources. Comprehensive and detailed, this work covers physical and mental health throughout the life cycle, with equal emphasis on women's and men's health." "Based on more than twenty years of patient care and contributions to medical education and community development, this resource will greatly heighten the quality of care that clinicians, health care practitioners, and educators can provide to their patients, and will in turn provide patients and consumers with the means to take an active role in their own health care."--Jacket